Political Islam in the age of democratization - Bokhari, Kamran; Senzai, Farid (Middle East today, 2013)
The continued prominence of Islam in the struggle for democracy in the Muslim world has confounded Western democracy theorists who largely consider secularism a prerequisite for democratic transitions. Kamran Bokhari and Farid Senzai offer a comprehensive view of the complex nature of contemporary political Islam and its relationship to democracy.